Myth, (New) History and Modernization of the Wild West - Ljubomir Hristić (University of Belgrade, 2016)
The western frontier has been, and persist in being a means of constructing and ascribing meaning partly due to its association with maps and mapped areas, and partly because of its appearance in a number of folk tales, manuscripts and in formal, scientific scrutiny, as a paradigmatic discourse shaped in the American tradition and beyond. In the paper, frontier of the American Wild West is analyzed through the structure in which it was used in relation to its mythical and historical occurrence, principally through its interpretation as a construct adjacent to common beliefs that the central, regular metaphors of this multidimensional concept differ, and yet, simultaneously, as it is presented, more often than not, are based on corresponding theoretical and methodological platforms.